A stakeholder driven engagement strategy to support the development of harmful algal bloom control technologies: A case study with DinoSHIELD - Alexandria G. Hounshell; Madison Horgan; Christopher L. Cummings; Elizabeth Staugler; Lynn E. Wilking; Alan J. Kennedy; Yanfei Wang; Kathryn J. Coyne; Kaytee L. Pokrzywinski (Environmental Challenges)
With rapid advancements in environmental technology, early stakeholder engagement in research and development is critical for successful technology transition. DinoSHIELD is a novel biological harmful algal bloom (HAB) control strategy that targets toxic dinoflagellates (e.g., Karenia brevis) through controlled release of a naturally-produced algicide from bacteria immobilized in non-toxic hydrogel. This study presents the first successful application of the Responsible Research and Innovation (RRI) framework to marine HAB control technology development. The stakeholder engagement strategy included workshops in southwest Florida with pre- and post-surveys to assess understanding and comfort, plus feedback sessions to gather actionable input for ongoing R&D. The RRI approach achieved measurable success across all objectives: survey results showed significant increases in stakeholder understanding (from ''fair'' to ''very good'') and comfort with DinoSHIELD, with 97 % of participants increasing understanding and 85 % increasing comfort. Stakeholder feedback directly informed critical R&D priorities including alternative deployment mechanisms, sustainability considerations, and ecological safety assessments, demonstrating successful framework responsiveness. Participants showed enthusiasm for the technology's natural derivation while identifying crucial research gaps that have been incorporated into ongoing development. This work establishes the first rigorous baseline of stakeholder perceptions for marine HAB control technologies and validates a replicable model for environmental management strategies. The results demonstrate that successful technology transition requires meaningful stakeholder participation throughout development, providing a template for accelerating responsible development of novel environmental technologies.